PERLINDUNGAN HUKUM KONSUMEN ATAS PENJUALAN TABUNG OKSIGEN PALSU SECARA ONLINE DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Angela Feblitania Emmanuella Hutauruk; Jeane Neltje Saly (Fakultas Hukum Universitas Tarumanagara, 2021)
In Law No. 8 of 1999 concerning Consumer Protection, it is explained that consumers have rights to goods and/or services that they obtain, both in direct transactions and online transactions, first in Article 4 paragraph (2) which explains the rights from consumers to choose goods and/or services and to obtain those goods and/or services in accordance with the exchange rate and conditions and guarantees for that matter are also contained in Article 8 which regulates prohibited actions for business actors which are not in accordance with the conditions of the guarantee, features or efficacy as stated in the label, label or description of the goods. but in this case the existing regulations have not been fully achieved as is often the case as in the case of selling fake oxygen cylinders online. The type of research used by the author in this study is normative. To support this research, the author uses a type of literature study research, which examines several related documents.